Melatonin in cryodiluent improves post-thaw quality andfertility of Murrah buffalo (Bubalus bubalis) bull spermatozoa - SINGH, P; SINGH, A K; DEVI, P; KUMAR, A; SINGH, N; RATTA, N S; SINGH, P (The Indian Journal of Animal Sciences, 2026)
The current research aimed to analyze the role of melatonin supplementation (0, 0.25, 0.5, 0.75 and 1.0 mM) on the freezability of buffalo bull spermatozoa. Thirty-six ejaculates were collected from six healthy bulls using artificial vagina. Only ejaculates with ≥70% progressive motility, ≤20% morphological defects and >500 million/ mL sperm concentration were selected for the study. Each ejaculate was diluted in Tris-egg yolk cryodiluent with selected concentrations of melatonin along with control and cryopreserved following established protocol. The post-thaw semen was assessed for sperm attributes and lipid peroxidation (LPO). IBM SPSS 22.0 software was used for statistical evaluations. The sperm total and progressive motility in post-thaw semen were evaluated using computer assisted semen analyzer (CASA) and were higher (P<0.05) in freezing media having 0.25 mM melatonin in comparison to other concentrations. The sperm viability and acrosome integrity were higher (P<0.05) at 0.25 mM melatonin concentration than at 0.75 mM, 1.0 mM and control. The sperm plasma membrane integrity among the experimental extenders supplemented with melatonin and control did not differ (P>0.05). All melatonin concentrations exhibited lower (P<0.05) MDA levels compared to control. The first service conception rate (FSCR) was higher (P>0.05) following inseminations using semen containing 0.25 mM melatonin than in control. Overall, the addition of 0.25 mM melatonin to the cryodiluent improved post-thaw semen quality of Murrah buffalo bulls.